Combination treatment of retinoic acid plus focal adhesion kinase inhibitor prevents tumor growth and breast cancer cell metastasis - Castro Guijarro, Ana Carla (2022)
All-trans retinoic acid (RA), the primary metabolite of vitamin A, controls the development and homeostasis of organisms and tissues. RA and its natural and synthetic derivatives, both known as retinoids, are promising agents in treating and chemopreventing different neoplasias, including breast cancer (BC). Focal adhesion kinase (FAK) is a crucial regulator of cell migration, and its overexpression is associated with tumor metastatic behavior. Thus, pharmaceutical FAK inhibitors (FAKi) have been developed to counter its action. In this work, we hypothesize that the RA plus FAKi (RA + FAKi) approach could improve the inhibition of tumor progression. By in silico analysis and its subsequent validation by qPCR, we confirmed RARA, SRC, and PTK2 (encoding RARα, Src, and FAK, respectively) overexpression in all breast cells tested. We also showed a different pattern of genes up/down-regulated between RA-resistant and RA-sensitive BC cells. In addition, we demonstrated that both RA-resistant BC cells (MDA-MB-231 and MDA-MB-468) display the same behavior after RA treatment, modulating the expression of genes involved in Src-FAK signaling. Furthermore, we demonstrated that although RA and FAKi administered separately decrease viability, adhesion, and migration in mammary adenocarcinoma LM3 cells, their combination exerts a higher effect. Additionally, we show that both drugs individually, as well as in combination, induce the expression of apoptosis markers such as active-caspase-3 and cleaved-PARP1. We also provided evidence that RA effects are extrapolated to other cancer cells, including T-47D BC and the human cervical carcinoma HeLa cells. In an orthotopic assay of LM3 tumor growth, whereas RA and FAKi administered separately reduced tumor growth, the combined treatment induced a more potent inhibition increasing mice survival. Moreover, in an experimental metastatic assay, RA significantly reduced metastatic lung dissemination of LM3 cells. Overall, these results indicate that RA resistance could reflect deregulation of most RA-target genes, including genes encoding components of the Src-FAK pathway. Our study demonstrates that RA plays an essential role in disrupting BC tumor growth and metastatic dissemination in vitro and in vivo by controlling FAK expression and localization. RA plus FAKi exacerbate these effects, thus suggesting that the sensitivity to RA therapies could be increased with FAKi coadministration in BC tumors.